Healing in the Sami North - Sexton, Randall Harold; Stabbursvik, Ellen Anne Buljo (Culture, Medicine, and Psychiatry, 2010)
The accepted version of this article is part of Randall H. Sexton's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/2450